(untitled) (Revista Venezolana de Salud Pública, 2018)
Parasitic diseases represent a public health problem worldwide, affecting all social classes, especially those lower socioeconomic strata. To determine the prevalence of intestinal parasites in different indigenous communities in the Zulia state, Venezuela, 232 fecal samples corresponding to individuals of both sexes, aged .